IMPLEMENTASI TRAFFIC ACCIDENT ANALYSIS (TAA) PADA KECELAKAAN LALU LINTAS BUS SANG ENGON DI SEMARANG - MURMUJANTOKO, MURMUJANTOKO (Dinamika Hukum, 2015)
Research objectives to provide an overview to the general, TAA is the sports scene things are implemented quikly, can be reconstructed and can be scientifically. Background is largely traffic accident investigator in the search for the cause of the accident early conclution only on the testimony of witnesses, who do not necessarily know the accident direcly. On the tourist bus traffic accident Engon police number B 7222 KGA which resulted in 18 people died in Semarang Jangli ring roads, traffic investigator have used the TAA if the crime scene. The research method used is qualitative method using sociological juridical approach, the nature of the research is descriptive analysis, primary data collection with interviews and observations, secondary data to examine the report, the literature. Data collection sites in Traffic Accidents Sub Section Contruction Area of Law Enforcement Traffic Police Directorate, Central Java region. Research results, in general TAA investigator have done according to regulations. Shortcamings in the shooting less detail. Cause of accidents because of drivers who ignore signs for signs. Kinematics calculation when entering corner bus vehicle speed of 100 kilometer per hour exceeds the safe speed of 40 kilometer per hour, so the bus overturned. The obstacles that the lack of understanding of the Law Number 22 of 2009 on traffic and road transport, investigators TAA has not skilled in shooting, no budget support improvement, people tent to want to know the condition of the crime scene and the public perception of the tool road as a freeway so driving at high speed. Advice in the thesis that firm action against dangerous traffic behavior, seek court approval for a driver^s licence revocation process driver, the need for the Deparment of Transportation to improve the color brighter and visible signs striking at night and during the day by choosing the best paint quality. Keywords: Traffic Accident Analysis, PC Recht, PC Crash